2012
DOI: 10.1177/014556131209100221
|View full text |Cite
|
Sign up to set email alerts
|

Ectodermal Dysplasia: Otolaryngologic evaluation of 23 Cases

Abstract: The aim of this prospective study was to improve the quality of life of and reduce morbidity for patients with ectodermal dysplasia by assessing their actual and potential ENT pathologies, and offering methods of prevention and treatment. The study was conducted between 2006 and 2008 and included 23 patients diagnosed with ectodermal dysplasia. The major symptoms of ectodermal dysplasia were evaluated. Patient histories were obtained in all cases, and a complete head and neck examination was carried out. Of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…While data are limited, these conditions can increase the frequency of cerumen impaction and the risk of otitis externa if present. 47…”
Section: Guideline Action Statementsmentioning
confidence: 99%
See 1 more Smart Citation
“…While data are limited, these conditions can increase the frequency of cerumen impaction and the risk of otitis externa if present. 47…”
Section: Guideline Action Statementsmentioning
confidence: 99%
“…While data are limited, these conditions can increase the frequency of cerumen impaction and the risk of otitis externa if present. 47 Narrowing of the ear canal limits visualization and increases the likelihood of trauma. A narrow ear canal makes both irrigation and manual instrumentation more difficult to perform.…”
Section: Supporting Textmentioning
confidence: 99%
“…Sweat glands and teeth of patients with HED are usually normal. But, sensorineural hearing loss, eye abnormalities, oral leukoplakia and diffuse eccrine poromatosis has been reported in a few cases …”
Section: Introductionmentioning
confidence: 99%
“…But, sensorineural hearing loss, eye abnormalities, oral leukoplakia and diffuse eccrine poromatosis has been reported in a few cases. 3,4 It has been demonstrated that mutation in gap junction beta 6 (GJB6) encoding Cx30 protein was determined in HED patients. To date, four mutations in GJB6 gene causing hidrotic ectodermal dysplasia have been found: G11R, V37E, A88V and D50N.…”
Section: Introductionmentioning
confidence: 99%
“…HED is a rare congenital genetic disorder with a birth incidence of 1/100,000-1/10,000 (2). It is characterized by the diminution or absence of eccrine sweat glands, oligodontia and peg-shaped teeth, and hair that is sparse and fine (1,3). Previous study indicates that X-linked HED (XLHED) is caused by mutations of the ectodysplasin A (EDA) gene at Xq12-13.1 (4).…”
Section: Introductionmentioning
confidence: 99%